Pengaruh Profitabilitas, Capital Intensity, dan Inventory Intensity pada Penghindaran Pajak - Dwiyanti, Ida Ayu Intan; Jati, I Ketut (E-Jurnal Akuntansi, 2019)
This study aims to determine the effect of profitability, capital intensity, and inventory intensity on tax avoidance. This research was conducted at manufacturing companies listed on the Indonesia Stock Exchange for the period 2015-2017 with a population of 150 companies. Determination of the sample in this research is by non probabilaty sampling method and by purposive sampling technique, so that the research sample is 63 companies. The data analysis technique used in this study is multiple linear regression analysis. Based on the results of multiple linear regression analysis which shows that all independent variables in this study, namely profitability, capital intensity, and inventory intensity have a positive effect on tax avoidance. Keywords: Profitability, capital intensity, inventory intensity, tax avoidance